Unveiling short-period binaries in the inner VVV bulge - Botan, E. (2021)
Most of our knowledge of the structure of the Milky Way has come from the study of variable stars. Among these variables, mimicking the periodic variation of pulsating stars, are eclipsing binaries. These stars are important in astrophysics because they allow us to directly measure the radii and masses of the components, as well as the distance to the system, thus being useful in studies of Galactic structure alongside pulsating RR Lyrae and Cepheids. Using the distinguishing features of their light curves, one can identify them using a semi-automated process. In this work, we present a strategy to search for eclipsing variables in the inner VVV bulge across an area of 13.4 deg2 within 1.68° < l < 7.53° and-3.73° < b <-1.44°, corresponding to the VVV tiles b293-b296 and b307-b310. We accurately classify 212 previously unknown eclipsing binaries, including six very reddened sources. A preliminary analysis suggests that these eclipsing binaries are located in the most obscured regions of the foreground disc and bulge of the Galaxy. This search is therefore complementary to other variable-star searches carried out at optical wavelengths.